2  If l1 , m1 , n1 and l 2 , m2 , n2 are the direction cosines of two mutually perpendicular lines, show that the direction cosines of the line perpendicular to both of these are m_{1}n_{2}-m_{2}n_{1}, n_{1}l_{2}-n_{2}l_{1},l_{1}m_{2}-l_{2}m_{1}.

Answers (1)

Given that l_1,m_1,n_1\ and\ l_2,m_2,n_2 are the direction cosines of two mutually perpendicular lines.

Therefore, we have the relation:

l_{1}l_{2}+m_{1}m_{2}+n_{1}n_{2} = 0                              .........................(1)

l_{1}^2+m_{1}^2+n_{1}^2 =1\ and\ l_{2}^2+m_{2}^2+n_{2}^2 =1         .............(2)

Now, let us assume l,m,n be the new direction cosines of the lines which are perpendicular to the line with direction cosines.l_1,m_1,n_1\ and\ l_2,m_2,n_2

Therefore we have, ll_{1}+mm_{1}+nn_{1} = 0 \and\ ll_{2}+mm_{2}+nn_{2} = 0

Or, \frac{l}{m_{1}n_{2}-m_{2}n_{1}} = \frac{m}{n_{1}l_{2}-n_{2}l_{1}} = \frac{n}{l_{1}m_{2}-l_{2}m_{1}}

\Rightarrow \frac{l^2}{(m_{1}n_{2}-m_{2}n_{1})^2} = \frac{m^2}{(n_{1}l_{2}-n_{2}l_{1})^2} = \frac{n^2}{(l_{1}m_{2}-l_{2}m_{1})^2}

\Rightarrow \frac{l^2+m^2+n^2}{(m_{1}n_{2}-m_{2}n_{1})^2 +(n_{1}l_{2}-n_{2}l_{1})^2+(l_{1}m_{2}-l_{2}m_{1})^2}    ......(3)

So, l,m,n are the direction cosines of the line.

where, l^2+m^2+n^2 =1                                   ........................(4)

Then we know that,

\Rightarrow (l_{1}^2+m_{1}^2+n_{1}^2)(l_{2}^2+m_{2}^2+n_{2}^2) - (l_{1}l_{2}+m_{1}m_{2}+n_{1}n_{2})^2

= (m_{1}n_{2}-m_{2}n_{1})^2 + (n_{1}l_{2}-n_{2}l_{1})^2+(l_{1}m_{2}-l_{2}m_{1})^2

So, from the equation (1) and (2) we have,

(1)(1) -(0) =(m_{1}n_{2}-m_{2}n_{1})^2 + (n_{1}l_{2}-n_{2}l_{1})^2+(l_{1}m_{2}-l_{2}m_{1})^2

Therefore, (m_{1}n_{2}-m_{2}n_{1})^2 + (n_{1}l_{2}-n_{2}l_{1})^2+(l_{1}m_{2}-l_{2}m_{1})^2 =1     ..(5)

Now, we will substitute the values from the equation (4) and (5) in equation (3), to get

\frac{l^2}{(m_{1}n_{2}-m_{2}n_{1})^2} = \frac{m^2}{(n_{1}l_{2}-n_{2}l_{1})^2} = \frac{n^2}{(l_{1}m_{2}-l_{2}m_{1})^2} =1

Therefore we have the direction cosines of the required line as;

l =m_{1}n_{2} - m_{2}n_{1}   

m =n_{1}l_{2} - n_{2}l_{1}

n =l_{1}m_{2} - l_{2}m_{1}

Exams
Articles
Questions